Método robusto para la alineación no rígida de imágenes médicas - Castellanos Abrego, Norma Pilar (Universidad Autónoma Metropolitana, 2004)
Recent attempts to improve non-rigid image registration have been focused on three aspects: modeling the geometric deformation field, searching techniques for the optimal model parameters, and defining similarity criteria, which establish the optimality of the numerical solution. The current trend is toward the development of hierarchical techniques, following a coarse-to-fine image analysis, in order to reduce the complexity of the search space when the images have not been previously processed. Several hierarchical techniques for nonrigid image registration classified in three incrementally complex strategies: 1) data-based, using scale space theory or pyramidal strategies with wavelet, gaussian, or spline functions; 2) warping model, incrementing the function coefficients (wavelet expansion or orthogonal basis functions) or the number of control points or landmarks in the image domain (splines or radial basis functions); and 3) the global model, assembled by different warping models. Warping models are classified by physical, when they are based on continuum mechanics theory; or by approximations to the deformation field by basis functions, polynomials or spatial transformations, with properties as continuity and differentiability. Among parametric models that describe the correspondence function using a global model with a relatively small number of parameters, local methods require more parameters that generally lead to more complicated optimization procedures, with the advantage of a more accurate warping. The combination of identifying complex intensity correspondences with a high dimensional geometrical transformation defines a search space arduous to traverse. In this thesis a method for nonrigid registration of images in two-dimensions (2D) is presented, when the intensity functional relationship is generally unknown. The global model is constructed in a hierarchical approach by the composition of spatial transformations, which are nonlinear and with a local domain. The dimension and number of the transformed domains depend on the application and the accuracy required in the global model. The spatial transformation generates a homotopy (a continuous function) between the affine map and the identity map, at the central and boundary positions of the domain, respectively. It means that the central position is mapped linearly to vanish smoothly toward the boundary, generating a continuous warping into a domain limited by a bounding circle. Thus, searching for the optimal global parameters of the warping model is a constrained nonlinear programming (NLP) problem that maximizes a voxel based similarity criterion. Constraints are employed to guarantee continuity, differentiability and a one-to-one transformation over the overlapping domain between the source and target images. We integrate evolutionary strategies into a hybrid algorithm adapted to use a variable mutation rate and to handle constraints. The hybrid algorithm uses the normalized mutual information as a cost function to maximize The main contribution to the state of the art is the introduction of a new spatial transformation, some remarks are needed to show the advantages and disadvantages of this approach in order to clearly understand its suitability for future applications. An advantage of the spatial deformation in the circular domain is that it requires only the parameters of the affine transformation, plus one that defines the smoothness of the warping model, for a total of five parameters for the 2D case. It defines a search space with a low dimensionality, which is independent of the circle spatial resolution. In comparison with other local methods that employ FFDs (Free Form Deformations) with B-Splines, wavelets Spline, Bézier-Splines or the viscous fluid model, our spatial transformation implicitly incorporates a function that defines a ROI (Region of Interest) where deformations are constrained to it, and the continuity at the boundary of the domain is guaranteed. The seed point which defines the center domain, can be localized anywhere the spatial resolution of the circle can allow the composition of local warpings, alleviating the need of uniformly spacing control points. We have not endorsed the problem of automatically localizing these points yet, which would involve several other techniques beyond the aim of this paper, but rather present experiments to show its potentiality. Besides, these technique do not compromise the dimensionality of the search space with the locality of the deformation, as with wavelets Spline, where the space is parameterized and the coefficients to optimize are increased to get more local deformations. This methodology is able to improve the similarity between image pairs based on a functional criterion and throughout multiple levels of resolution, from coarse to fine. To prove the above mentioned, we have designed several experiments on synthetic and real images, the former with the objective that the reader can observe clearly the evolution of the composition of local warps for simpler images, the latter to show the robustness of the method for simulated deformations in brain RM, temporal comparison of chest Rx, multimodality registration of PET-CT of chest and human to mandrill face deformation. For all these image pairs we measure its similarity with NMI at each level of resolution and evaluate by visual inspection the difference image as accuracy is not intended in this work and this issue must be addressed in an application-based context.; La investigación actual en las técnicas de alineación no rígida de imágenes (nonrigid image registration) está concentrada en tres grandes áreas: 1) La proposición de modelos de deformación geométrica de la imagen, 2) La estrategia de búsqueda de los parámetros óptimos del modelo, y 3) El criterio de similitud que cuantifica la calidad de la solución numérica. Todas ellas se concentran en una propuesta metodológica para resolver el problema de alineación no-rígida entre pares de imágenes o volúmenes. En el caso de una solución basada en los voxeles de la imagen, lograr la correspondencia de las intensidades entre pares de imágenes complejas, en conjunto con un modelo de deformación de dimensión alto, define un espacio de búsqueda muy difícil de atravesar hacia la solución óptima global. Actualmente se emplean estrategias jerárquicas para lograr disminuir la complejidad de los espacios de búsqueda. Cuando se establece una jerarquía en la exposición de los datos, la imagen se analiza en un esquema de global a local, tal que jerárquicamente se introduzcan cada vez más detalles de la imagen. Como contribución a la línea de investigación, la presente tesis desarrolla un método para la alineación no rígida de imágenes en 2D basada en la composición de transformaciones no lineales con control local. En particular, se introduce un nuevo modelo para la deformación geométrica de imágenes. La principal ventaja de este modelo con respecto a otros reportados en la literatura, es que la transformación espacial propuesta define implícitamente el dominio de la transformación, que en esta primera versión es circular pero puede adaptarse a otras formas geométricas. Además, cada transformación llevada a cabo dentro del dominio global o local, requiere de la optimización de únicamente cinco parámetros, simplificando la dimensionalidad del espacio de búsqueda. Aunque el método no se dirige a una aplicación clínica específica, pretende que el usuario final pueda realizar la alineación no rígida entre dos regiones de interés (ROI-Region of interest) identificadas manual o automáticamente, sin perturbar a las regiones vecinas fuera del dominio y sí manteniendo la continuidad en el límite del mismo. La transformación espacial genera una homotopía entre una deformación afín y la identidad, en las posiciones central y límite del dominio, respectivamente. Esto es, se define una función suave y no lineal a través del dominio circular, la cual es gobernada por cuatro parámetros que definen el tipo de deformación y uno extra, llamado el parámetro de suavidad, que establece el grado de diferenciabilidad de la función. Los cinco parámetros de la transformación son analizados rigurosamente para garantizar diferenciabilidad, continuidad en el límite del dominio y la correspondencia uno-a-uno de la transformación espacial. Así, el problema de alineación no rígida se establece como un problema de optimización no lineal con restricciones no lineales, que busca los parámetros óptimos globales de la transformación al maximizar la información mutua normalizada. La optimización no lineal se lleva a cabo con un algoritmo genético híbrido adaptado para emplear una velocidad de mutación variable y el manejo de restricciones. El método general de alineación no rígida está definido por una función de deformación global compuesta por la composición de transformaciones no lineales y locales, en un esquema jerárquico de global a local, con la intención de evitar lidiar con la complejidad de un espacio de búsqueda global. Para validar la metodología se realizaron pruebas en imágenes sintéticas y reales. Para el caso en imágenes sintéticas, se generaron deformaciones con parámetros conocidos, permitiendo la validación con el parámetro verdadero (ground truth). En las imágenes reales no se dispone de esta información por lo que sólo se evalúa la consistencia del método y se analiza cualitativamente y cuantitativamente la imagen diferencia resultante. También se aplica el procedimiento en las deformaciones entre rostros, de un humano a mandril y viceversa, a manera de probar la robustez del método en un contexto fuera del marco de las aplicaciones médicas. En todos los casos es posible apreciar tanto cuantitativa como cualitativamente el incremento en la similitud del par de imágenes conforme aumenta el número de transformaciones y el nivel de resolución del dominio de transformación. Aunque la técnica propuesta no ha sido empleada en alguna aplicación específica, se considera que los experimentos seleccionados son adecuados para demostrar la robustez de la técnica para diversas formas geométricas.